Cut-Off Value of Procalcitonin in Sepsis and Septic Shock patients at Dr. Soetomo Hospital - Shinta Lungit Ambaringrum; Yetti Hernaningsih; Edward Kusuma; Hartono Kahar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Sepsis is a state of life-threatening organ dysfunction caused by dysregulation of the body's response to infection. Organ dysfunction is marked by an increase in SOFA score ≥ 2 or qSOFA score ≥ 2. Septic shock is a subset of sepsis with fairly severe circulatory disorders that can significantly increase mortality. Although the current gold standard diagnosis method for sepsis is bacterial culture, some researchers believe PCT can help identify sepsis severity because bacterial culture requires a relatively long time. This study aims to determine the cut-off point of procalcitonin in patients with sepsis and septic shock. The data taken were secondary data from the medical records of sepsis and septic shock patients in Dr. Soetomo General Hospital from 2017 to 2019. Determination of cut-off PCT for sepsis and septic shock using Receiver Operating Characteristic (ROC) analysis curve. Most sepsis patients were young (18 - 65 years) (69%) (p = 0.331) and male (60%) (p = 0.156). The majority of the clinical sepsis patients have focal infections of the respiratory system (55.17%). Patients with respiratory tract infections who develop sepsis have an OR of 6.182, which means it is six times more likely to develop septic shock. There was a significant difference between septic and non-septic PCT levels (p = 0.000), and there was a positive correlation between PCT and sepsis. The cut-off of procalcitonin in sepsis was 0.6 ng/mL, and the cut-off of procalcitonin in septic shock was 10 ng/mL.